ANALISIS PERBEDAAN FUNGSI PARU PADA MASYARAKAT BERISIKO BERDASARKAN KEPADATAN LALU LINTAS DAN KADAR DEBU TOTAL AMBIEN DI JALAN KOTA SEMARANG - Annisa Amilush Shalihah; Nurjazuli Nurjazuli; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Semarang as one of the big cities in Indonesia has a high vehicle volume growth, which is 8% each year with road growth of 2-5% each year. It has an impact on increasing the number of motor vehicles and produce vehicle exhaust emissions. Parking attendants, street vendors, security guards, tire treadmillers are potential to be exposed to the dust generated by vehicle exhaust emissions. The study aimed to analyze the difference of lung function (prediction value of FVC and FEV1) on community at risk based on traffic density and total ambient dust concentration on Semarang City street. This research used observational analytic research with cross-sectional approach. The study was conducted on three streets of Semarang City (Pemuda, Dr. Sutomo, and Brigjend Sudiarto) with 45 community at risk determined by purposive sampling as respondents. The results of dust concentration by measurement (Pemuda=345 μgr/Nm3, Dr. Sutomo=345 μg/Nm3, Brigjend Sudiarto=193 μgr/ Nm3). Measurement of traffic density as VCR value (Pemuda=0.52, Dr. Sutomo=0.64, Brigjend Sudiarto=0.36). While the measurement of lung function on community at risk using spirometry (μ FVC=78.00, σ FVC=16.845 and μ FEV1=83.78, σ FEV1=18.126), and other data obtained by observation. Data were analyzed using one way anova test with (α=0,05). The statistical test result of FVC prediction value (df=44; p=0,125) and FEV1 prediction value (df=44; p=0,393) rata-rataing no difference (prediction value of FVC and FEV1) on community at risk based on traffic density and total ambient dust concentraton on three streets of Semarang City.